(untitled) (Revista Electrónica Calidad en la Educación Superior, 2018)
Internal entrepreneurship has to do with personal and social values, such as responsibility, initiative, creativity, flexibility, teamwork, leadership, ability to take risks, flexibility and cooperation. External entrepreneurship is oriented to the creation of businesses. Reference will be made from Costa Rica, as part of an investigation carried out by the Academic Research of OPES, with respect to entrepreneurship based on the results of the assessment of the academic and professional development expectations consulted to graduates of the Biology discipline (196) from the state universities, as well as advanced students of the discipline in question (109). For the discipline in Biology and according to the investigation of the Academic Division, what refers to entrepreneurship as an option to enter the world of work is not the aspiration of the majority and there is no expectation of forming a company of its own, nor working as an independent professional or to dedicate itself to the advisory area. The expectations that are most outlined from the beginning to the end of the training, since they are evidenced by both the advanced students and graduates of the Biology discipline, have to do with obtaining a postgraduate degree, dedicating themselves to research and working in a public institution, in other words, be salaried. It seems important for Costa Rica to be able to add value to the solid training provided in the area of Basic Sciences in state universities, especially in the discipline of Biology and to be able to develop, along with the culture of academic excellence, culture of entrepreneurship.